Keterampilan Memecahkan Masalah Santri Pada Tahun Pertama di Pondok Pesantren. - Fatimah, Siti (2016)
The aims of this research are to understand and describe about the student's perception about Islamic boarding school, problem solving skill of student in the first year at Islamic boarding school, factors that affect a problem solving skill of student, impact that will be faced by student in problem solving. Informants in this research were taken by using purposive sampling technique, especially for students of PPMI Assalaam and PPA Al-Muayyad, class of VII Junior High School, 12-14 years old, amount to twelve people and taking data used an interview. The results of the research are: 1) student's perception about Islamic boarding school is a place where inhabited by a lot of students to train independence, study about religion and fortify a self from bad intercommunication. 2) Problems that faced by student in the first year at Islamic boarding school are adaptation, friendship, obedience towards rules, activities problems. Obtained data that student skilled in friendship, obedience towards rules, activities problem, but less skilled in solving adaptation problem. 3) Factors that support the subject in solving problem are internal factors covering religious, psychologist and conditional aspect and external factors covering friend influence, Islamic boarding school staff, and parents. While the inhibit factors are internal factors covering forget, lazy and ignored and external factor is negative influence from friend. 4) Impacts for student who face the problems in the first year live at Islamic boarding school are worse relations with friend, student got sick, cry often, lessons interrupted and want to move school. The conclusion of the research is requiring a good support from friend, teacher, and also family in helping a student to solve the problem. By student has skill in solving problem then student will get a lot of advantages such student can solve the problem, student can do positive things in Islamic boarding school and student will be easier to live the new life in Islamic boarding school.